Parametric vibration analysis and validation for a novel portable hexapod machine tool attached to surfaces with unequal stiffness. (November 2019) - Ma, Nan; Dong, Xin; Palmer, David; Arreguin, Josue Camacho; Liao, Zhirong; Wang, Mingfeng; Axinte, Dragos
Abstract: The Free-Leg Hexapod (Free-Hex) machine tool is an advancement from the conventional Stewart platform, which has the fixed base platform removed to enable the limbs to be attached to a wider range of surfaces (e.g. non-flat and curved). However, in some scenarios (e.g. in-situ repair of industrial installations), the limbs of the Free-Hex need to be attached to the surfaces with unequal stiffness, which brings the challenge of predicting the dynamics of the system for conducting machining operations under dynamically stable conditions. In this paper, after introducing the attachment stiffness (i.e. feet attached to the environment with different materials) in the conventional dynamic model of the parallel manipulator, the dynamic behavior of the Free-Hex machine tools devoted to the in-situ operation environments was studied. Then, the experimental validation was conducted to prove the dynamic model developed in this paper. It was found that the errors of the proposed model are under 6% (i.e. 5.1% at symmetrical limb configuration and 5.8% at the arbitrary configuration) when the limbs are attached to the surfaces with unequal stiffness. Further, by applying the validated model, the dynamic performance of the Free-Hex with a wider range of attachment stiffness was analyzed. Overall, it was found that the attachment stiffness has a remarkable influence on the natural frequencies of the machine tool (e.g. the frequency of mode 4 at the symmetrical configuration is increased by 36.8% when the attachment stiffness of one limb changes from 0 to 1e+12 N/m). Thus, the work discussed in this paper can be utilized to avoid the dynamically unstable configurations of parallel kinematic machine tools (e.g. Free-Hex) when mounting on the surface with unequal stiffness in the in-situ operation environments.